Foot-core stability in non-hemorrhagic stroke: A case report: A Case Report - Yulia Dini Wahyuni; Arif Pristianto; Elif Nur Efendi (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Introduction: Stroke is a neurological deficit or apoplexy that occurs suddenly due to vascular disturbances. Exercise delivery, the function of the foot-core system (foot-core stability), and the potentially beneficial effects of training have received increasing attention in the clinical and athletic fields because of the critical role of the intrinsic leg muscles as local stabilizers and direct sensors of foot deformation. Case description: The research was a case study of an elderly patient aged 67 years diagnosed with hemiparesis non-hemorrhagic stroke. This case was taken at the Magetan Physiotherapy Clinic from December 7 to December 27, 2022. Physiotherapy problems in this case included pain, muscle weakness, limited joint motion, and impaired standing balance. Results: The results obtained after administering physiotherapy interventions and exercise therapy can improve the functional abilities of the body experiencing weakness, increase proprioception in patients and provide foot-core stability that can help with problems. Conclusions: Physiotherapy interventions with exercise therapy could increase proprioception and provide foot-core stability for stroke patient’s with severe disability.